Marine-Derived Products for Biomedicine - Giovine, Marco (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The sustainable exploitation of marine biodiversity is one structural column of the "blue economy", and the discovery of new compounds and materials to be used in biomedicine is considered one of the most strategic activities, within an economic context. An exhaustive selection of the different typologies of approaches used by marine biotechnologists to develop research on these topics are demonstrated in the eight original articles and two reviews comprising this Special Issue. The reported scientific publications describe the discovery of new compounds for cancer therapy or for the control of bacterial virulence. Different new uses of marine chitin or chitosan-based materials are also shown for the first time, as well as novel green techniques for the extraction of compounds from marine algae or from fishery waste, which are described in the two reviews.